Diagnosis of distributed faults in outer race of bearings via Park's transformation method - Irfan, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
The Park's transformation method has been used in this paper to analyze distributed defects in the outer race of the bearing. The existing non-invasive motor current analysis and instantaneous power analysis methods are unable to detect distributed defects in the bearings, due the fact that characteristics defect frequencies models are not available for these type of bearing defects. Thus, this paper proposes a graphical approach based on the Park's transformation of three phase current to analyze bearing distributed defects. The theoretical and experimental work conducted shows that the proposed method can detect bearing distributed defects without use of any extra hardware. The results on the real hardware implementation confirm the effectiveness of the proposed method. Â© 2015 IEEE.